The effects of periodic overloads on fatigue crack growth in a pearlitic Grade 900A steel used in railway applications. (September 2020) - Masoudi Nejad, Reza
Highlights: This paper is to predict a three-dimensional fatigue crack growth path in the presence of periodic overloads. The Maximum Tangential Stress crack extension criterion is used to obtain the propagation paths. The stress intensity factor is estimated using the Crack Opening Displacement approach. The crack growth rate is predicted utilizing the Forman–Newman–de Koning model. Comparison between experimental and numerical results has shown a good agreement. Abstract: The objective of this paper is to predict a three-dimensional fatigue crack growth (FCG) in a pearlitic Grade 900A steel used in railway applications in the presence of periodic overloads. Numerical and experimental methods are used to investigate the behavior of FCG in the rail specimens. A 3-D boundary element model, using the BES tool is used to estimate the stress intensity factor (SIF) using the crack opening displacement (COD) approach in rail specimens. Also, the crack growth rate is predicted utilizing the Forman–Newman–de Koning (FNK) model. Linear elastic fracture mechanics (LEFM) is used to predict the fatigue life developed from a two-stage fatigue loading cycle where both mechanical loads and periodic overloads are present. The maximum tangential stress (MTS) crack extension criterion is used to obtain the FCG paths. The results revealed that fatigue life is highly sensitive to periodic overloads. Therefore, this factor significantly affects the fatigue life of railway rails during service conditions. In the present investigation, the periodic overloads have remained constant and the effect of load ratio and the number of overloads on the fatigue life has been investigated.